FAKTOR PENYEBAB PENGEDARAN RUPIAH PALSU DI INDONESIA - Margamu Desy Putri Dewi; Ade Adhari (Jurnal Hukum Adigama, 2021)
This legal research discusses the factors that cause the circulation of counterfeit rupiah in Indonesia. The research method used is normative legal research and empirical legal research. The research approach in this legal research uses a state approach. The legal approach is carried out by examining the laws and regulations related to the causes of the circulation of counterfeit Rupiah. Sources of data used are primary data and secondary data. The legal materials used to support secondary data are primary legal materials such as the Criminal Code (KUHP), Law Number 7 Year 2011 concerning Currency, Bank Indonesia Regulation Number 21/10/PBI/2019 concerning Rupiah Money Management. The data analysis technique used is descriptive by using deductive thinking. Based on the research conducted, there are factors that cause someone to counterfeit rupiah currency, namely economic factors, seeking personal gain, low education, opportunities to do so, high movement, and technological developments. Based on the factors that cause counterfeiting and circulation of rupiah which should be used as a reference to eliminate the factors that trigger the occurrence of the crime of counterfeiting money because in preventing a crime, eliminating the causes is the best prevention.